Do fast retinal oscillations play a role in vision? A study in the anesthetized and awake cat - Manços, Giovanne de Rosso (2015)
Early physiologists were dazzled by the occurrence of high-amplitude, periodic oscillations, easily discernible in recording traces from the eye, optic tract and optic ganglia. Numerous studies thereafter pointed to retinal ganglion cell as the elements responsible for the generation of these fast rhythms, which were known to propagate to the lateral geniculate and to the cortex. Only recently, however, these early observations gained renewed interest, mainly in the light of recent theories linking neuronal oscillations to various cognitive processes, such as perceptual binding, attention and memory. In this context, fast retinal oscillations have been associated to the binding of contiguous contours or surfaces, which in principle could support a fast feedforward segmentation process. In addition, a series of experiments in the cat have shown that fast oscillations in the retina may convey global stimulus properties, such as size. A limitation in these previous studies, however, was that most of them where were made in the anesthetized and paralyzed cat. Only a few early studies have been performed in the non-anesthetized but still paralyzed cat. Another concern was that, in these latter experiments, visual stimuli were often limited to ganzfeld flashes, far from natural vision conditions. Moreover, very recently we made the surprising observation that fast retinal oscillations depend strongly on halothane (and isoflurane) anesthesia. It was therefore imperative to verify whether oscillatory activity is also present in the awake cat, under naturalistic conditions, such as during free-viewing of a visual scene. This is the main goal of the present study. Simultaneous multiple-electrode recordings were made from the lateral geniculate nucleus (LGN) and the retina of anesthetized cats (N= 3) and from the LGN of an awake cat (N= 1). Comparisons were made for responses to natural movies and flashed stationary light stimuli. To test specifically the role of retinal oscillations in encoding stimulus size we designed a protocol made of a light circle of varying size along the trial. Spike sorting techniques allowed us to study separately the ON- and OFFcomponents of the responses. Analysis consisted in measuring synchronous oscillations for single cell spiking activity in the time (sliding correlation analysis) and spectral domains (multitaper spectral analysis, multitaper coherence). Our present results based on single-cells extend our previous findings in the anesthetized cat, which were restricted to an autocorrelation analysis of LGN mutiunitary responses. Both ON- and OFF-responses to varying size stimuli show that coherent oscillations appear only after the stimulus attained a minimum size of about 5° (depending on the contrast level), suggesting that oscillations in the retina are rather limited in encoding subtle changes in stimulus size. Recordings obtained directly from eye showed that oscillations in the retina, as in the LGN, are highly correlated with the concentrations level of halothane. Notably, in a series of sessions we were able to record LGN responses in an awake cat, which was subsequently anesthetized with halothane, keeping the same recording site. Oscillations were completely absent in the awake condition and appeared strong as usual during the halothane anesthesia. Overall these results weaken substantially the notion that fast retinal oscillations are meaningful for vision. Nevertheless, as shown from our single cell analysis, retinal oscillations share many of the properties of cortical gamma oscillations. In this respect, oscillations in the retina induced by halothane serve as a valuable preparation, even though artificial, for studying oscillatory neuronal dynamics.